Exploring the dynamics of Programmed Death-Ligand 1 in canine lymphoma: unraveling mRNA amount, surface membrane expression and plasmatic levels - Ubiali, Alessandra; Cesar Conti, Luiza; Dall’Ara, Paola; De Maria, Raffaella; Aresu, Luca; Moretti, Pierangelo; Sini, Federica; Riondato, Fulvio; Stefanello, Damiano; Comazzi, Stefano; Martini, Valeria (Frontiers in Veterinary Science, 2024)
Introduction Programmed Death-Ligand 1 is a well-known immune checkpoint molecule. Recent studies evaluated its expression in different canine cancer types through different laboratory techniques. The present study aims to evaluate the surface membrane protein expression (mPD-L1) by means of flow cytometry (FC) in different canine lymphoma immunophenotypes. Furthermore, in a subset of cases, mRNA and plasmatic soluble protein (sPD-L1) have been assessed in the same patient, and correlations among results from the three analyses investigated. Methods Samples obtained for diagnostic purpose from untreated dogs with a confirmed lymphoma immunophenotype were included: surface protein was assessed via FC and quantified with median fluorescence index ratio (MFI ratio), gene expression was evaluated by real time quantitative polymerase chain reaction (RT-qPCR) and plasmatic concentration of soluble protein (sPD-L1) measured with ELISA. Statistical analyses were performed to investigate any difference among FC immunophenotypes, updated Kiel cytological classes, and in the presence of blood infiltration. Results Considering FC, most B-cell lymphomas (BCL) were positive, with higher MFI ratios than other subtypes (81%, median MFI ratio among positive samples = 1.50, IQR 1.21–2.03, range 1.01–3.47). Aggressive T-cell lymphomas had a lower percentage of positive samples (56%) and showed low expression (median MFI ratio in positive samples = 1.14, IQR 1.07–1.32, range 1.02–2.19), while T-zone lymphomas (TZL) were frequently positive (80%) but with low expression (median MFI ratio in positive samples = 1.19, IQR 1.03–1.46, range 1.02–6.03). Cellular transcript and sPD-L1 were detected in all samples, without differences among immunophenotypes. No correlation between results from different techniques was detected, but sPD-L1 resulted significantly increased in FC-negative lymphomas (p = 0.023). Discussion PD-L1 molecule is involved in canine lymphoma pathogenesis, with differences among immunophenotypes detected by FC. Specifically, BCL have the highest expression and aggressive T-cell lymphomas the lowest, whereas TZL need further investigations.